Exploring the Process of Creating and Managing Personal Political Brand Identities in Nonparty Environments: The Case of the Bailiwick of Guernsey. Issue 4 (1st October 2020) - Pich, Christopher; Armannsdottir, Guja; Dean, Dianne
Abstract: How do you create and build a personal political brand? Personal branding can enable individuals to self-commodify and formulate distinct identities created from both tangible and intangible characteristics. However, there is little insight into how individuals create and manage their personal brand identities. This paper contributes to this lacuna in the literature and focusses on personal political branding. Contextualized in the British Crown Dependence of Guernsey; the island community has no political parties and Parliamentarians [deputies] stand as independent candidates. Deputies construct their own personal brand with the aim of resonating with their constituents often with limited resources and without the 'political machine' found in party-systems. Therefore, this study examines the deputies' strategies to create, build and communicate their brands in a nonparty system. Findings indicate that Guernsey's politicians created their desired identities around key components including legacy, heritage and experience, personality characteristics opposed to focused policies, personal values and acknowledged that brand building was a continuous process of maintaining presence, and communicating personal aspirations. Therefore, Guernsey's politicians formulated their personal political brand identities without the mechanisms of a party system. This paper extends the personal branding literature demonstrating the challenging process of formulating and managing personal political brands in a competitive environment and presents a Personal Brand Identity framework, a strategic tool to evaluate and refine desired identities within and beyond the setting of politics.